The competitive landscape in transitioning countries: The example of the Armenian wine industry - Linda Bitsch; Barbara Richter; Jon Hanf (Wine Economics and Policy, 2022)
Scholars showed that in transition and developing countries originating from the Soviet period, the degree of market competition is rather low, as large corporates that had been operating were still prevailing. One can assume that the markets had been highly attractive and many newcomers must have been interested in entering the market, due to fewer market participants, i.e. processors and retailers, but numerous farmers are engaged in the commodity production. This had provoked relatively high profitability for downstream firms acting on the local market and likely increased the market competition. However, evidence exists that market structures and hence competition is still hampered. Therefore, this study aims to show how competition in markets of transition countries has developed and provide a detailed description of the market structure to derive the degree of competition. As the subject of research, the Armenian wine industry has been exemplarily chosen as its wine industry is emerging and represents a key sector in the Armenian agri-food industry. Similar cases exist in other transitioning and developing countries. Empirical results from the qualitative research that allows a comprehensive overview of the whole sector reveal that the competition intensity is relatively low, and wine producers act in an oligopolistic market surrounding. Based on this, implications for producers and policy makers are derived, which include competitive and rural policy implications.
Keywords: 330; Armenia; competition intensity; industry structure; policy implications; rural development; wine